2019
DOI: 10.2298/abs181129039x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol blocks atherosclerosis development by inhibiting IL-1β in macrophages induced by cholesterol

Abstract: blocks atherosclerosis development by inhibiting IL-1β in macrophages induced by cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recent studies have also shown that the anti-atherosclerotic effect of berberine may be through the activation of the Sirt1-TFEB or AMPK/mTOR signaling pathway to induce autophagy and inhibit the inflammatory response of macrophages [ 96 , 97 ]. In addition to inducing autophagy, resveratrol could inhibit the inflammation of Ana-1 murine macrophages caused by cholesterol, inhibit the expression of IL-1β in macrophages and enhance the reverse cholesterol transport of macrophages [ 98 ]. An in vivo study also shows that ApoE −/− mice with 24 weeks of oral resveratrol eliminate intestinal fatty acids and monoglycerides accumulation in atherosclerotic lesions [ 99 ].…”
Section: Tuning Macrophages For Atherosclerosis Therapymentioning
confidence: 99%
“…Recent studies have also shown that the anti-atherosclerotic effect of berberine may be through the activation of the Sirt1-TFEB or AMPK/mTOR signaling pathway to induce autophagy and inhibit the inflammatory response of macrophages [ 96 , 97 ]. In addition to inducing autophagy, resveratrol could inhibit the inflammation of Ana-1 murine macrophages caused by cholesterol, inhibit the expression of IL-1β in macrophages and enhance the reverse cholesterol transport of macrophages [ 98 ]. An in vivo study also shows that ApoE −/− mice with 24 weeks of oral resveratrol eliminate intestinal fatty acids and monoglycerides accumulation in atherosclerotic lesions [ 99 ].…”
Section: Tuning Macrophages For Atherosclerosis Therapymentioning
confidence: 99%